Diabetes Mellitus Affecting Arteriovenous Fistula (AVF) (The Planet, 2024)
Introduction: Diabetes is one of the main contributors to chronic kidney disease (CKD) and end-stage renal disease (ESRD), conditions that often require hemodialysis. An arteriovenous fistula (AVF), a connection surgically created between an artery and a vein, is the preferred vascular access method for dialysis due to its longevity and lower risk of infection. AVF outcomes in diabetic patients are often compromised due to diabetes-related vascular issues, including endothelial injury arterial calcification and reduced blood flow. Aim of the study: The study aimed to evaluate the risk factors contributing to AVF, focusing on the history of diabetes in these patients. Methods & Materials: This observational study was conducted at Dhaka Medical College Hospital (DMCH) to assess AVF outcomes in CKD stage 5 and ESRD patients needing AVF construction. Eighty-two participants, meeting specific inclusion and exclusion criteria, were enrolled from January 2019 to July 2020. Clinical history, physical examination, and peripheral pulse assessments were performed. Blood samples were taken for various lab investigations. Following AVF construction, patients were closely monitored every 7-10 days and evaluated in weeks six and ten for AVF status. Result: In a study involving 82 patients, the arteriovenous fistula (AVF) failure rate was found to be 28%, while 72% of AVFs functioned successfully. Patients in the failure group were slightly older (mean age 47.13 years) and had a higher body mass index (BMI) (24.66 kg/m²). The failure group exhibited significantly lower systolic (SBP) and diastolic blood pressure (DBP) compared to the functioning group. Notably, diabetes mellitus (DM) was present in 73.9% of the failure group, with smoking and BMI also correlating significantly with AVF failure. Increased BMI and smoking were associated with higher odds of AVF failure, emphasizing the need for careful patient management. Conclusion: This study reveals that diabetes significantly increases the early failure rate of arteriovenous fistulas (AVFs) in CKD and ESRD patients, with a 28% failure rate. Key risk factors include high BMI, smoking, and low diastolic blood pressure (DBP), while age and serum creatinine levels showed no significant differences.
Keywords: Diabetes; Arteriovenous fistula (AVF); chronic kidney disease (CKD); End-stage renal disease (ESRD)